Workshop Pembuatan dan Publikasi Artikel Ilmiah di Jurnal atau Prosiding untuk Dosen dan Mahasiswa - Dona Fitriawan; Dede Suratman; Edy Yusmin; Ahmad Yani T.; Dian Ahmad Budhysatrya; Romal Ijuddin (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACTThis service activity began with the publication conditions of lecturers and students which were felt to be very lacking in both proceedings and journals on a national and international scale in West Kalimantan. This form of service is a workshop or training "to create and publish scientific articles in journals or proceedings for lecturers and students at STKIP Singkawang". This workshop was attended by lecturers and final semester students at STKIP Singkawang. The method for creating and publishing this article includes: 1) adapting the published article to applicable writing rules, 2) creating published article guidelines in the form of an opening, introduction, discussion, research methodology, research results, conclusion, and supporting sections. The subjects of this activity were students and lecturers of the mathematics education study program at STKIP Singkawang. The product of this activity is the publication of scientific works for lecturers and students. Data collection techniques include observation, interviews and documentation techniques. The stages of this service activity are: 1) Preparation: determining the location and obtaining permission to carry out this workshop activity; 2) Implementation: holding workshops, analyzing test results, and assisting with the preparation and publication of scientific articles, conducting workshops in class; 3) Final: The output of this activity is an article published in a national journal. The result of this service is the holding of workshop activities in accordance with the steps that have been determined and the holding of guest lectures with STKIP Singkawang. Keywords: Workshop, Publication, Journal or Proceeding   ABSTRAKKegiatan pengabdian ini berawal dari kondisi publikasi dosen dan mahasiswa yang dirasa sangat kurang baik dalam prosiding maupun jurnal skala nasional dan internasional di Kalimantan Barat. Bentuk Pengabdian ini adalah workshop atau pelatihan “membuat dan mempublikasikan artikel ilmiah pada jurnal atau prosiding bagi dosen dan mahasiswa di STKIP Singkawang”. Workshop ini diikuti oleh dosen dan mahasiswa semester akhir di STKIP Singkawang. Cara pembuatan dan penerbitan artikel ini meliputi: 1) menyesuaikan artikel publikasi dengan kaidah penulisan yang berlaku, 2) membuat pedoman artikel publikasi berupa pembukaan, pendahuluan, pembahasan, metodologi penelitian, hasil penelitian, penutup, dan bagian pendukung. Subyek kegiatan ini adalah mahasiswa dan dosen program studi pendidikan matematika di STKIP Singkawang. Produk dari kegiatan ini berupa publikasi karya ilmiah bagi dosen dan mahasiswa. Teknik pengumpulan data berupa teknik observasi, wawancara, dan dokumentasi. Adapun tahapan kegiatan pengabdian ini adalah: 1) Persiapan: penentuan lokasi dan mendapatkan izin pelaksanaan dalam kegiatan perbengkelan ini; 2) Pelaksanaan: mengadakan lokakarya, menganalisis hasil tes, dan membantu persiapan dan persiapan publikasi artikel ilmiah, melakukan lokakarya di kelas; 3) Final: Keluaran dari kegiatan ini adalah artikel yang diterbitkan dalam jurnal nasional. Hasil dari pengabdian ini adalah terselenggaranya kegiatan workshop sesuai dengan langkah-langkah yang telah ditetapkan dan terselenggaranya kuliah tamu bersama STKIP Singkawang. Kata Kunci: Workshop, Publikasi, Jurnal atau Prosiding